Faktor Internal Penentu Laju Pertumbuhan Modal Sendiri pada Perusahaan Rokok Go Public di Bursa Efek Indonesia - Wahyu Wiyani; Eko Yuni Prihantono; Roos Widjajani; Harril Brimantyo (University of Merdeka Malang, 2020)
This study aims to analyze the effect of the basic earning power, debt to equity ratio, plowback ratio, and interest and tax rate on the growth rate of equiy in cigarette companies that go public on the Indonesia Stock Exchange in 2013-2018. Data analysis technique used is multiple linear regression. The results showed that the four variables had a simultaneously significant effect on the growth rate of equity, while only Basic Earning Power had no significant effect partially. Because the calculation of basic earning power uses Earning Before Interest and Tax where Earning Before Interest and Tax is the profit that has not been taxed, which in fact tax for cigarette companies is a large expense. In addition, equity growth itself is largely determined by the amount of Earning After Tax compared to Earning Before Interest and Tax. The higher the Earning After Tax, the greater the opportunity for equity growth.